دراسة العلاقة بين إدارة المسار الوظيفي والالتزام التنظيمي دراسة ميدانية على الشركات الصناعية في الساحل السوري - غدير, باسم; عمران, عمران (Latakia University Journal - Economic and Legal Sciences Series, 2016)
هدفت هذه الدّراسة إلى التّعرف على تأثير إدارة المسار الوظيفي ومجموعة من المتغيّرات الديموغرافية على الالتزام التّنظيمي للعاملين في عدد من الشّركات الصّناعيّة في السّاحل السّوري، حيث اتبع الباحث المنهج الوصفي الّذي يناسب طبيعة البحث، وتمّ الاعتماد على عيّنة ميسّرة تتألف من (100) عامل في الشّركات المذكورة، وتم تحليل البيانات واختبار الفرضيّات باستخدام البرنامج الحاسوبي SPSS الإصدار 20. توصّلت هذه الدّراسة إلى مجموعة من النّتائج أهمّها: وجود علاقة ارتباط طرديّة وضعيفة بين إدارة المسار الوظيفي والالتزام التّنظيمي في الشّركات محل الدّراسة، حيث أظهرت هذه الدّراسة وجود علاقة ارتباط طرديّة وضعيفة بين (التّرقية، والإثراء الوظيفي، والتّدريب) والالتزام التّنظيمي، كما أظهرت هذه الدّراسة عدم وجود فروق جوهرية بين إجابات أفراد العينة حسب الجنس والعمر، أي لايوجد فروق بين إجابات الذّكور والإناث، كما لايوجد فروق بين إجابات أفراد العينة حسب الشّرائح العمريّة.This study aimed to identify the impact of career management and demographic variables on organizational commitment of employees in a number of industrial companies in the Syrian coast, where the researcher followed the descriptive approach that fits the nature of the research, was relying on deliberate soft sample of (100) factor in the companies mentioned, data were analyzed and test hypotheses using a computer program SPSS 20. the researcher concluded to the following results: there is a positive and a weak correlation between the career management and organizational commitment in the companies under study, and this study found a positive and a weak correlation between the (promoting, job enrichment and training) and organizational commitment, and This study found no significant differences between the answer of respondents by sex and age, witch mean there is no differences between male and female responses, and there is no differences between the answer of the respondents according to age groups.